1986
DOI: 10.1210/endo-119-5-2306
|View full text |Cite
|
Sign up to set email alerts
|

Human Platelet-Derived Transforming Growth Factor-βStimulates Parameters of Bone Growth in Fetal Rat Calvariae*

Abstract: Human platelet-derived transforming growth factor type beta (TGF beta) is mitogenic for fetal rat calvariae in serum-free organ culture. It enhances DNA synthesis in short (24-h) and long (48- to 96-h) term cultures, but produces no significant stimulatory effects on bone collagen synthesis or alkaline phosphatase activity (two parameters of differentiated osteoblastic cell-type function) when present continuously in culture. Transitory treatment with TGF beta, however, induces a subsequent stimulation of coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(62 citation statements)
references
References 26 publications
3
58
0
1
Order By: Relevance
“…Interleukin-1, which has limited amino acid sequence homology with acidic FGF (31), stimulates bone resorption and has stimulatory effects on collagen synthesis in 24-h cultures, whereas in 96 h cultures it is inhibitory and these effects are temporarily opposite to those of ECGF (32,33). Transforming growth factor-,B is the only growth factor that has effects resembling those of ECGF on bone formation, but it has been shown to stimulate bone resorption in mouse calvariae, an effect not reported in fetal rat long bones (26,34).…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-1, which has limited amino acid sequence homology with acidic FGF (31), stimulates bone resorption and has stimulatory effects on collagen synthesis in 24-h cultures, whereas in 96 h cultures it is inhibitory and these effects are temporarily opposite to those of ECGF (32,33). Transforming growth factor-,B is the only growth factor that has effects resembling those of ECGF on bone formation, but it has been shown to stimulate bone resorption in mouse calvariae, an effect not reported in fetal rat long bones (26,34).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-P has also been shown to promote cartilage and bone growth when introduced subperiosteally (Noda and Camilliere, 1989;Joyce et al, 1990). The target of such TGF-p action may be mesenchymal cells, chondrocytes, preosteoblast, osteoblasts, and/or osteocytes (Centrella, 1986;Sporn and Roberts, 1990;Noda and Camilliere, 1989;Joyce et al, 1990;Massague, 1990). It has been shown that TGF-P acts through regulation of ECM synthesis (Rizzino, 1988;Massague, 1990;Sporn and Roberts, 1990), e.g., increasing the expression of fibronectin (Ignotz and Massague, 1986;Dean et al, 1988) and collagen (Seyedin et al, 1987;Ingotz and Massague, 1986;Roberts et al, 1986;Varga et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…For example, rhBMP-2 increases ALP activity in C26, W-20-17, MC3T3-E1 cells, whereas TGF-β1 inhibits it [4,11,22]. Further, TGF-β1 does not appreciably affect cells in organ culture of rat calvariae [3]. These results suggest that TGF-β1 may not be a suitable agent to induce differentiation in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 92%
“…β1 are varied because the effect of TGF-β1 depends on the characteristics of the cell, namely whether it is tumorderived, its species of origin, and the stage of cell differentiation [3,4,11]. For example, rhBMP-2 increases ALP activity in C26, W-20-17, MC3T3-E1 cells, whereas TGF-β1 inhibits it [4,11,22].…”
Section: Discussionmentioning
confidence: 99%